The Factors of Investment Security in Iran - Mohammadhossein hosseinzadeh Bahreini (جستارهای اقتصادی, 2004)
The amount of investment in any economy depends on a number ofinvariables one of the most important of which is the security ofinvestment. The amount of investment and the causes of lack ofsecurity for investing can be viewed from two sides:١. The objective approach to security in which attempts are made tounderline the objective invariables which indicate how efficientthe institutions responsible for maintaining security are.٢. The subjective approach to security in which attempts are made torealize the degree of security in a country, the causes of lack ofsecurity, the influence of each of these causes on marketing ingeneral. In order to be able to form an idea about all this, theactual investors are interviewed. The logical idea of investigatingsecurity through this approach is to provide investors with asubjective view of how safe it is to invest so that they can decidewithout feeling worried.The article is mainly concerned with the factors of insecurity ofinvestment in Iran in the light of the report written by internationalorganizations. It discusses the conditions of marking in Iran and thedegree of risks in it. The account which the report introduces ismainly based on the second approach.